Karakteristik Varietas Unggul Kacang Tanah dan Adopsinya oleh Petani - Kasno, Astanto; Harnowo, Didik (Iptek Tanaman Pangan, 2014)
Improved variety of peanut has an important role as a component technology in the production improvement program. However, the adoption of improved varieties of peanuts is still lack behind, when to be compared with those of rice or hybrid maize. Adaptive local varieties of peanut are still dominating the crop area, although improved varieties have higher productivity, mature earlier, and tolerant to some biotic and abiotic stresses. Out of 34 officially released varieties, consisting of 26 spanish type and 8 valencia type, only a few are popular to peanut farmers. Relatively old varieties, namely Gajah (released in 1950) and Kelinci (released in 1986) are more accepted by farmers compare to the newly released varieties. Approximately 50 percent of the peanut crop area are planted with local varieties. Seed unavailability and high seed price during the planting time seems to be the factors causing the slow of new variety adoption, coupled with the lack of information regarding new varieties from the extension agent to farmers. Very low seed multiplication rate (10 kg of seed obtained from 1 kg seed planted) and rapid loss of seed germination, has discouraged seed producers from providing peanut seed to farmers. Preference for kernel characteristics among user (industries, consumers, traders, farmers) need to be elucidated to match the characters of improved varieties to be developed through the breeding program. The capacity of providing breeder seed (BS) by the Indonesian Legumes and Tuber Crops Research Institute (ILETRI) was only about 15% of the total required, needs to be improved. To back up the existing seed movement among fields and seasons, peanut estate needs to be developed, especially in the peanut production centres. Concerted efforts involving farmers group, agricultural services, extension agent and traders, are required to push peanut productivity.